POTRET DIRI WANITA MUSLIMAH (Studi Fenomenologi Wanita Pekerja Karet di Desa Kuala Mandor B Kabupaten Kuburaya) - Muhammad Munir; Dwi Putri Robiatul Adawiyah (PSGA LP2M IAIN Pontianak, 2021)
Islam perceives muslim women who obedient to Allah and His prophet. This is an implementation of amar ma'ruf nahi mungkar values written in the Qur'an and Hadith. In this research an extreme work was done by Muslim women, their courage in doing slicing the bark of rubber tree to get the latex (noreh) alone in the middle of the night located in the forest.This work really made the researchers amazed.It was interesting to be adopted by all women moslem that they can learnin and understand the life of a Muslim woman that happened in the village clearly. The method of the study uses descriptive qualitative research and the approach is Phenomenology Study, using data collection methods: interviews, observation and documentation, which include Muslim women, rubber workers, and including the people in the village. The location of this study is in the village of Kaula Mandor B, Kuburaya Regency by snowball regardingMuslim women plays an important role in family such as parenting children, obeying their husbands and their parents. While in data analysis, researchers would analyze, explore data. Data analysis is directed at research questions, data reduction, and synthesis. Triangulation and extension of participation is used as checking the validity of the data. The results of this study are the role of Muslim women, the courage of Muslim women, the upbringing of Muslim women, and self-portraits of Muslim women in Islam.